Analisis Destination Image Stasiun Lambuang sebagai Objek Wisata Kuliner Kota Bukittinggi - Genzia Aurela Joya Islami; Dwi Pratiwi Wulandari (Jurnal Manajemen Pariwisata dan Perhotelan, 2025)
This research was conducted because there are problems regarding the destination image at Stasiun Lambuang Bukittinggi. The aim of this research is to analyze the destination image of Stasiun Lambuang as a culinary tourist attraction in Bukittinggi City. This research uses quantitative descriptive methods, with observation techniques and distributing questionnaires to 130 visitors to Stasiun Lambuang obtained by non-probability sampling techniques, with judgment sampling type. The research instrument was a questionnaire which was analyzed using SPSS 25.00. The results showed that the destination image of Stasiun Lambuang was classified as very good with a respondent achievement level of 87.91%, due to the factors of Quality of Experiences, Tourist Attractions, Environment and Infrastructure, Entertainment and Outdoor Activities, Cultural Traditions, Tourism Resources, Facilities, Supporting Factors, Tourism Environment, Service Quality, Cognitive Image, Unique Image, and Affective Image as forming the positive image, on average are rated well by respondents.With improved facilities, services and a wider promotional strategy, Stasiun Lambuang has the potential to become increasingly developed as a leading culinary tourism destination in Bukittinggi City.